Low cost SCADA system with auto fault detection using micro controller - Shah, M. Azman; Al-Khateeb, Khalid A. Saeed; Mohammad, M. F. (2005)
A low cost Supervisory Control and Data Acquisition (SCADA) system has been developed with an auto fault detection capability. The PLC used in a standard SCADA system has been eliminated by using a microprocessor chip, resulting in a lower cost. Signals derived from a large number of detectors and sensors can be processed simultaneously. The design enables the system to check the alarm status, true or false, i.e. normal, faulty sensor or open circuit. The data acquisition circuit is interfaced with the microcontroller board to evaluate the current flow conditions, normal or abnormal. A program written in Visual Basic provides for a graphical layout of the plan of the plant or building to be displayed on the monitor with a clear indication of the alarm spot. A close circuit television (CCTV) camera is made to move automatically to capture the particular location of the triggered alarm at the same time of the alarm signal.